Cement-free algae mud plate and preparation method thereof
By using a cement-free formula and high-temperature, high-pressure autoclaving technology, lightweight and high-strength diatomaceous earth boards are prepared, solving the problems of high density and low purification efficiency of existing diatomaceous earth boards and realizing the industrial application of healthy building materials.
Patent Information
- Application Number
- CN202511794449.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-16
- Filing Date
- 2025-12-02
- Publication Date
- 2026-01-20
AI Technical Summary
Existing diatomaceous earth panels have high density, which is not conducive to industrial production and installation. The addition of cement causes efflorescence and ablation of the finish, resulting in low purification efficiency. They are also unsuitable for ceiling installations and other similar applications.
Using a cement-free formula, including short fiber pulp, medium and long fiber pulp, diatomaceous earth, quartz sand, hydrated lime, wollastonite, metal elements and rod stone, tobermorite crystals are generated through high-temperature and high-pressure autoclaving, forming lightweight and high-strength diatomaceous earth boards.
This invention achieves lightweight, high-strength diatomaceous earth panels with excellent sound insulation and formaldehyde purification capabilities, meeting healthy building standards, reducing material costs and carbon emissions, and making them suitable for various building scenarios.
Smart Images

Figure CN121362021A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of plate materials, and particularly relates to a cement-free diatom ooze plate and a preparation method thereof. BACKGROUND
[0002] Diatom ooze is a very well-known healthy material for decoration, which is non-toxic and harmless in itself, and is currently mainly used in the field of building decoration in the form of diatom ooze paint applied on walls. Although the health characteristics of the material are responded, the finishing effect has not been broken through.
[0003] The existing diatom ooze plate has a density generally greater than 1.2, which is not conducive to industrial production, finishing review and on-site installation, and requires a high labor strength, and the yield is also very low. The addition of cement in the plate will cause efflorescence and burn the finishing surface after being wet. More specifically, the content of diatom ooze is relatively low (generally about 15%), and the purification efficiency and capacity are greatly reduced. In addition, due to the relatively high specific gravity, the diatom ooze plate cannot be applied to the ceiling and other scenes. SUMMARY
[0004] The present application aims to provide a cement-free diatom ooze plate and a preparation method thereof to solve the problems in the background art.
[0005] To achieve the above-mentioned purpose, the present application provides the following technical scheme: A cement-free diatom ooze plate is composed of the following materials by mass fraction: Short fiber pulp 6-8%, medium and long fiber pulp 2.5-3.5%, diatomite 32-38%, quartz sand 24-28%, slaked lime 18-22%, wollastonite 5-7%, metal elements 2.5-3.5%, barium 0.5-1%, and pure water, wherein the pure water is added to a beating consistency of 10-12%.
[0006] Preferably, the silicon content of the diatomite is not less than 85wt%; The mesh number of the quartz sand is 300-400 mesh; The beating degree of the pulp is 45-55, and the wet weight is 8-12; The calcium hydroxide content of the slaked lime is more than 90wt%, and the mesh number is 200-300 mesh; The metal elements are one or more of iron, zinc, titanium, nickel, and silver.
[0007] The present application also provides a preparation method of the cement-free diatom ooze plate, comprising the following steps: S1, pumping short fiber pulp and medium and long fiber pulp into a beater, adding quartz sand, diatomite, and slaked lime, and finally adding the remaining materials to fully stir to form a slurry; S2, the slurry is sent to a slurry storage tank, and is uniformly supplied to a further mixing mill for further mixing, and then is sent to a pre-mixing tank for pre-mixing treatment, and the quality concentration of the slurry is detected and the flow is adjusted; S3, the slurry obtained in the step S2 is uniformly flowed out through a headbox and is laid on a running industrial conveying belt, water is filtered by a vacuum system, a thin material layer is wrapped around a forming cylinder, and when the material layer reaches a set thickness, the material is cut, the corners are removed, and the material is transported to a material receiving machine, and a stacker is used to alternately stack a template and a material. S4, the wet material stack obtained in the step S3 is pre-cured to make the board reach a preliminary strength, and the pre-cured board is sent to a demolding machine for demolding and stacking; S5, the demolded board is pulled into a steam autoclave through a steaming trolley and a traction machine, and is subjected to steam autoclaving, and under high temperature and high pressure, the silicon dioxide, calcium hydroxide and water in the board are subjected to hydration reaction, and finally tobermorite crystals are generated; The steam autoclaving includes temperature rising, constant temperature, temperature falling, and the constant pressure is 1.0-1.5 MPa; S6, the board stack trolley with the steam curing pad out of the steam autoclave is separated from the autoclaved board and the steam curing pad by a board suction machine, and the autoclaved board is continuously dried by a drying machine to make the water content of the board reach below 9.5%; S7, the dried board is subjected to thickness setting by a double-sided sanding machine, and is subjected to edge grinding and chamfering treatment by an edge grinding and chamfering machine.
[0008] Preferably, in the step S4, the pre-curing time is 12-24 hours.
[0009] Preferably, in the step S5, the steam autoclaving includes temperature rising for 2-3 hours, constant temperature for 8-12 hours, and temperature falling for 2-4 hours.
[0010] Compared with the prior art, the present application has the following beneficial effects: (1) Without adding cement, the structural strength of the board is not affected, the destruction of some components in the cement to the later finishing composite material is avoided, the carbon emission in the production process is reduced, and the weight and cost of the material itself are also reduced.
[0011] (2) The cement-free algal mud board is subjected to high temperature and high pressure steam autoclaving treatment, stable tobermorite crystals are generated, the durability and stability of the material are improved, the material is not easy to deform and crack in use, and long-term sound insulation effect can be maintained. BRIEF DESCRIPTION OF DRAWINGS
[0012] Figure 1 The process flowchart of the present application is shown. DETAILED DESCRIPTION
[0013] The application provides a cement-free algal mud plate which is composed of the following materials in mass fraction: Short fiber pulp 6-8%, medium-long fiber pulp 2.5-3.5%, diatomite 32-38%, quartz sand 24-28%, slaked lime 18-22%, wollastonite 5-7%, metal elements 2.5-3.5%, barite 0.5-1% and pure water, wherein the pure water is added to a beating consistency of 10-12%.
[0014] In the application, the beating degree of the short fiber pulp and the medium-long fiber pulp is 45-55, and the wet weight is 8-12.
[0015] In the application, the fiber size of the short fiber pulp is preferably less than or equal to 1.2 mm, and specifically can be 0.5-1.2 mm, and the fiber size of the medium-long fiber pulp is preferably 1.5-2 mm.
[0016] In the application, the silicon content of the diatomite is not less than 85 wt%, the diatomite is preferably active diatomite, the particle size of the active diatomite is less than 100 nm, and the titanium dioxide content is 1-5 wt%.
[0017] The grinding process of the active diatomite and the common diatomite is different, the grinding particle size of the active diatomite is less than 100 nm, and the high temperature generated during grinding can oxidize the trace titanium elements contained in the diatomite, thereby generating 1-5% of titanium dioxide, while the particle size of the common diatomite is usually in microns, and no titanium dioxide is generated during grinding. The common diatomite is more focused on the basic physical adsorption function, and after the pollutants are saturated, they may be re-released when the temperature rises or the humidity decreases, causing secondary pollution; while the active diatomite can simultaneously play the physical adsorption and chemical decomposition roles, the titanium dioxide in the active diatomite can play the role of photocatalyst, the photocatalyst can generate strong oxidizing substances under the action of light, which can completely oxidize and decompose the formaldehyde, bacteria and viruses adsorbed in the pores of the diatomite into harmless carbon dioxide and water, thereby solving the problem of secondary pollution. The results of the embodiments show that the formaldehyde purification efficiency of the algal mud plate provided by the application can reach more than 95%; at the same time, the photocatalyst can damage the cell wall of bacteria and the protein of viruses, thereby playing a sterilization role and inhibiting the growth of mold from the root. In summary, the active diatomite is adopted in the application, and the algal mud plate prepared by the application is a functional plate which meets the requirements of the room health standard.
[0018] In the application, the mesh number of the quartz sand is 300-400 mesh, and specifically can be 350 mesh.
[0019] In the application, the calcium hydroxide content of the slaked lime is more than 90 wt%, and the mesh number is 200-300 mesh, and specifically can be 250 mesh.
[0020] In the present application, the metal element is one or more of iron, zinc, titanium, nickel and silver; in the present application, the metal element can be a metal element brought by other raw materials or a metal element additionally added; by controlling the content of metal elements such as iron, zinc, titanium and nickel, the present application can ensure the effect of the plate on optimizing air quality; silver ions can perform contact sterilization and can also play a sterilization role in darkness, complementing the active diatomite (sterilization under light) to play a double composite antibacterial role.
[0021] In the present application, the attapulgite specifically refers to attapulgite, which has a unique nanofibrous structure and strong adsorption capacity. When the attapulgite is dispersed in water, the tiny fibers will interleave and lap with each other to form a three-dimensional network structure, which can lock a large number of water molecules and greatly hinder the free flow of liquid, thereby showing high viscosity, so that the slurry remains viscous and does not settle when at rest. In the present application, attapulgite is used to replace cement and gypsum, so that the preparation of algae mud plate can be realized under the condition of no cement and no gypsum, and the weight of the algae mud plate is reduced on the basis of ensuring the strength. In the specific embodiments of the present application, if the attapulgite is omitted, the slurry cannot be formed. By omitting cement and gypsum, the present application can reduce the weight of the plate, and subsequent veneering does not need to be permeated and crystallized on the plate surface. Moreover, the omission of gypsum also avoids the introduction of oxidized sulfur, thereby avoiding the influence of the plate on human health.
[0022] In the present application, the wollastonite is a natural calcium silicate mineral, usually in the form of needles or fibers. In the present application, wollastonite is used as a filler to play a role in strengthening and toughening, improve the mechanical properties of the product, and increase the wear resistance. Compared with cement, gypsum and other materials, wollastonite does not cause skin and inhalation injury when in contact with the human body, and meets the international WHO health building standards for formaldehyde, organic volatile matter, air humidity, temperature, noise and other environmental requirements that affect the health of residents.
[0023] The present application also provides a cement-free algae mud plate preparation method, comprising the following steps: S1, pump the short fiber pulp and the medium-long fiber pulp into a beater, add quartz sand, diatomite, slaked lime, and finally add the remaining materials, and fully stir to form a slurry; S2, send the slurry to a slurry storage tank, quantitatively and uniformly supply it to a grinding machine for further mixing, then send it to a pre-mixing tank for pre-mixing and processing, detect the mass concentration of the slurry and adjust the flow rate; S3, the slurry obtained in step S2 is uniformly discharged from a headbox and laid on a running industrial conveyor belt, water is filtered by a vacuum system, a thin material layer is wrapped around a forming cylinder, and when the material layer reaches a set thickness, the blank is cut off, the corners are removed, and the blank is transported to a blank receiving machine, and a stacking machine is used to stack one template and one blank alternately. S4. Pre-curing the wet blanks stacked in step S3 to achieve early strength, and then sending the pre-cured blanks to the demolding machine for demolding and stacking. S5. The demolded slab is pulled into the autoclave by the oxygen steaming trolley and the traction machine for autoclaving. Under high temperature and high pressure, the silica, calcium hydroxide and water in the slab undergo a hydration reaction, and finally tobermorite crystals are generated. The autoclaving process includes heating, maintaining a constant temperature, and cooling, with the constant pressure being 1.0-1.5 MPa; S6. The trolley with the steam curing pads coming out of the autoclave is separated from the autoclaved slabs and steam curing pads by the suction plate machine. The autoclaved slabs are then continuously dried by the dryer to bring the moisture content of the slabs down to below 9.5%. S7. After drying, the slab is sanded to a certain thickness using a double-sided sander, and then the edges are ground and chamfered using an edge grinding and chamfering unit.
[0024] In this invention, the pre-curing time in S4 is 12-24 hours.
[0025] In this invention, in step S5, autoclaving includes heating for 2-3 hours, maintaining a constant temperature for 8-12 hours, and cooling for 2-4 hours.
[0026] In this invention, the final temperature of the heating during the autoclaving process is 380~420℃, preferably 400℃.
[0027] This invention, by controlling the autoclaving process, enables calcium hydroxide and silicon dioxide to react fully. Simultaneously, autoclaving under high temperature and pressure conditions expands the particle size of the diatomaceous earth, increasing its activity and enhancing its high-temperature resistance, thus enabling it to degrade harmful substances in the air under normal temperature and sunlight conditions. Furthermore, high-temperature and high-pressure autoclaving increases the porosity of the diatomaceous earth board, thereby improving its sound absorption, energy storage, and moisture absorption capabilities.
[0028] Furthermore, the autoclaving temperature for traditional diatomaceous earth boards is around 200℃, and excessively high temperatures can reduce the board's strength. This invention, however, incorporates medium-length fiber pulp and employs a special autoclaving process to avoid the impact of short fiber breakage under high temperature and pressure on structural strength, thus ensuring the board's strength under these conditions. Moreover, boards produced under this invention's high temperature and pressure do not require subsequent surface penetration crystallization treatment to achieve the necessary surface bonding strength. In contrast, traditional diatomaceous earth boards require surface penetration crystallization treatment to meet the bonding strength requirements for decorative veneers. However, this treatment severely damages the board's microporous structure, affecting its breathability, moisture absorption, acoustic properties, and ability to degrade harmful substances—all essential functions required to meet healthy building indoor air quality standards—resulting in a significant loss of the board's actual functionality.
[0029] The technical solutions of the present application will be described below with reference to the embodiments. It should be apparent that the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work fall within the scope of the present application.
[0030] Embodiment one: Please refer to Figure 1 As shown in the figure, a cement-free diatom ooze board is composed of the following materials with mass fractions: 6.5% of short fiber pulp, 3.5% of medium-long fiber pulp, 35% of diatomite, 25% of quartz sand, 20.7% of slaked lime, 6% of wollastonite, 2.5% of metal elements, 0.8% of barite, and pure water, and the pure water is added to a beating concentration of 11%.
[0031] The diatomite contains not less than 85wt% of silicon; the mesh number of the quartz sand is 350 meshes; the beating degree of the short fiber pulp and the medium-long fiber pulp is 50, and the wet weight is 10; the calcium hydroxide content of the slaked lime is not less than 90wt%, the mesh number is 250 meshes, and the metal element is titanium.
[0032] A cement-free diatom ooze board preparation method comprises the following steps: S1, pumping the fiber material into a beater, then adding quartz sand, diatomite, slaked lime and other materials, and finally adding auxiliary materials for improving functions, fully stirring the powdered materials and paper pulp in a stirrer to prepare a slurry, and sending the slurry to a slurry storage pool for standby use; S2, the slurry in the slurry storage pool is uniformly supplied to a double-disc beater by a pump, and the slurry is further mixed, then sent to a slurry storage machine for standby use, and the well-beaten slurry is sent to the slurry storage machine for pre-mixing and stirring under the conditions of set weight, concentration, and other technical requirements, so as to detect the quality concentration of the slurry and adjust the flow size; The constant slurry concentration can stabilize the operation of the flow slurry board machine, and facilitate the adjustment of the board thickness; S3, the slurry is uniformly discharged from the flow box and laid on the running industrial conveying belt, the water is filtered by the vacuum system, the thin material layer is wrapped around the forming cylinder, and when the material blank thickness reaches the set value, the blank is cut off, the edge material is removed, and the blank is transported to the blank receiving machine, and the stacking machine is used to stack the blank and the template alternately; The forming cylinder with a certain diameter is selected for the board making machine, and the blank is cut after cutting to form a blank with a size larger than the standard blank (standard blank: 1220mmx2440mm); The servo motor is used for the stacking machine, which can accurately control the speed and positioning accuracy; The height of the maintenance trolley and the template trolley is actively regulated by two elevators, and the whole process of plate making, blank joining and stacking is automatically controlled; S4, after the wet blank is stacked, pre-maintenance is performed to make the blank reach the early strength, and the pre-maintained blank is sent to a demolding machine for demolding and stacking; S5, the demolded blank is pulled into a steam pressure kettle through a plate stack on a steam trolley by a traction machine for steam pressure maintenance, under high temperature and high pressure, the silica, calcium hydroxide and water in the blank are hydrated to finally generate tobermorite crystals; The demolded template is cleaned by a cleaning and oiling machine and then stacked on a trolley to return to the stacking machine along the track for recycling. The blank is then transferred to the front of the steam pressure kettle by a transfer vehicle and grouped into the kettle; The blank enters the steam pressure kettle and is maintained under high temperature and high pressure; The steam pressure process includes temperature rising, constant temperature and temperature falling, and the steam pressure program is: temperature rising for 2 hours, constant temperature for 10 hours after temperature rising to 400℃, and temperature falling for 3 hours. The constant pressure is controlled to be 1.28MPa during the steam pressure process; The kettle needs to be vacuumized before steam pressure, and the vacuumization is performed to-0.48atm, which is more conducive to saving steam, uniform heat absorption of the board, good air permeability and avoiding steam curing defects; S6, the well-steam-cured blank is continuously dried by a drying machine to make the moisture content of the blank below 9.5%; The blank is continuously dried in a tunnel kiln by the drying machine, the hot air is circulated in the kiln by an axial flow fan, and the blank is uniformly dried; The plate stack trolley with steam curing pads taken out of the steam pressure kettle separates the plate and the steam curing pad by a plate suction machine; The plate taken out of the drying machine is unloaded by a plate belt conveyor, a positioning roller conveyor and a vacuum plate suction machine, and then stacked into a pile, and then sent into a semi-finished product storage area by a forklift; S7, in order to ensure the flatness of the plate surface, sanding and edge grinding are adopted to strengthen the appearance quality, and the dried blank also needs to pass through a double-sided sander to fix the thickness, and the sanded plate is further ground and chamfered by an edge grinding and chamfering machine.
[0033] In this embodiment, the pre-maintenance time in S4 is 12 hours.
[0034] Example Two The difference from Example One is that a cement-free alginate board is composed of the following materials with mass fractions: short fiber pulp 8%, medium-long fiber pulp 3%, diatomite 33%, quartz sand 27%, slaked lime 21%, wollastonite 5%, metal elements 2.5%, barite 0.5% and pure water, the pure water is added to a beating concentration of 10%, and the rest is the same as Example One, which is not repeated here.
[0035] Example Three The difference from Example 1 is that a cement-free diatomite board is composed of the following materials by mass fraction: pulp (short fiber) 8%, pulp (medium-long fiber) 3.5%, diatomite 32%, quartz sand 25%, slaked lime 20%, wollastonite 7%, metal elements 3.5%, barite 1%, and pure water, the pure water is added to a pulp concentration of 12%, and the rest is the same as Example 1, which is not repeated here.
[0036] Application Test Example Combustion Test: The diatomite board in Example 1 is tested for combustion performance (including single test items such as in-furnace temperature rise, mass loss rate, sustained combustion time, and total heat value), apparent density, water absorption, radioactivity, heavy metal content, and formaldehyde purification efficiency, and the specific results are as follows: Table 1 Performance Test Results Where: not detected means: formaldehyde release <0.10 mg / L; hexavalent chromium content <1 mg / kg; cadmium content <5 mg / kg; mercury content <5 mg / kg.
[0037] In addition, the sound insulation and sound absorption coefficient of the board obtained in Example 1 are tested according to GB / T19889.3-2005 "Acoustics - Measurement of the sound insulation properties of buildings and of building elements - Part 3: Laboratory measurement of airborne sound insulation of building elements" and GB / T20247-2006 "Acoustics - Reverberation room measurements of sound absorption in a reverberation room", and the test environment is controlled within the temperature range of 20-25℃ and the humidity range of 50-60%RH, the results show that the sound insulation is 52db, and the sound absorption coefficient is about 0.91.
[0038] After testing, the diatomite board sample provided by the example of the present application meets the technical requirements of A (A1) grade non-combustible material (product) in GB8624-2012 "Combustion performance classification of building materials and products", indicating that it has excellent combustion performance. At the same time, the density of the board is low, the formaldehyde purification effect is good, and the sound insulation and sound absorption effect is good.
[0039] The flexural strength of the diatomite boards obtained in Examples 1-3 is tested, and the results show that they are all greater than 12MPa; the apparent density of the diatomite boards obtained in Examples 2-3 is tested, and the results show that Example 2 is 0.76g / cm 3 , and Example 3 is 0.81g / cm 3 .
[0040] Comparative Example 1 The other conditions are the same as in Example 1, and only the addition of barite is omitted, and the results show that the slurry cannot be shaped, the initial setting effect cannot be achieved, and the board cannot be obtained.
[0041] Comparative Example 2 Other conditions and embodiment 1 are same, only change the end point temperature of temperature rise in steam pressure curing to 200 DEG C, the result shows that the strength of board material greatly reduces.
[0042] In summary, the application removes cement as the main disadvantageous material of structure coagulation, increases the adding amount of diatom ooze to 35%, and the density of the obtained algae ooze board is as low as 0.5-0.9 g / cm 3 The efficiency and capacity of purifying formaldehyde and organic volatile substances are (97% or more within 2-6 hours), the release level of negative ions is dozens of times higher than that under the relative condition, the sound insulation reaches 52 decibels, the sound absorption efficiency reaches 0.91, the energy storage effect is also very obvious, the energy saving level is particularly prominent compared with other materials, and the product is a model product in the field of building materials, carbon emission and carbon neutralization; the composite of other materials does not need to be treated by permeation crystallization, and will not have negative influence on the adsorption performance of diatom ooze; the water absorption level can reach 60% or more, the water storage and humidity balance effect on the indoor are good, the indoor negative oxygen ions are positively excited and mutually achieved; the light mass density can adapt to the application in the whole field of building decoration, reduces the physical consumption of labor, and has more positive significance for the health of laborers.
[0043] Although the embodiments of the present application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made thereto without departing from the principles and spirit of the present application, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A cement-free algal sludge board, characterized in that, consists of the following materials by mass fraction: short fiber pulp 6-8%, medium long fiber pulp 2.5-3.5%, diatomite 32-38%, quartz sand 24-28%, slaked lime 18-22%, wollastonite 5-7%, metal elements 2.5-3.5%, barite 0.5-1%, and pure water, the pure water is added to a beating concentration of 10-12%.
2. The cement-free algal mud plate according to claim 1, characterized in that: the silicon content of the diatomite is not less than 85wt%; the mesh size of the quartz sand is 300-400 mesh; the beating degree of the short fiber pulp and the medium long fiber pulp is 45-55, and the wet weight is 8-12; the calcium hydroxide content of the slaked lime is more than 90%, and the mesh size is 200-300 mesh; the metal elements are one or more of iron, zinc, titanium, nickel, and silver.
3. The cement-free algal mud plate according to claim 1, characterized in that, The diatomite is active diatomite.
4. A process for the production of cement-free algea board, characterized in that, The method comprises the following steps: S1, pumping short fiber pulp and medium long fiber pulp into a beater, adding quartz sand, diatomite, and slaked lime, and finally adding the remaining materials, and fully stirring to form a slurry; S2, sending the slurry into a slurry storage tank, quantitatively and uniformly supplying a grinding machine for further mixing, and then sending it into a pre-mixing tank for pre-mixing and processing, detecting the mass concentration of the slurry and adjusting the flow; S3, uniformly flowing the slurry obtained in step S2 through a headbox onto an industrial conveyor belt in operation, vacuum filtering water through a vacuum system, and surrounding the slurry on a forming cylinder in a thin layer, cutting the blank when the multiple layers of surrounding reach a set thickness, removing the corners, and conveying the blank to a blank receiver, using a stacker to alternately stack a template and a blank; S4, pre-curing the wet blank stacked in step S3 to make the blank reach the early strength, and sending the pre-cured blank to a demolding machine for demolding and stacking; S5, after demolding, the blank is pulled into a steam autoclave through a steam oxygen trolley and a traction machine for steam autoclaving, under high temperature and high pressure, the silicon dioxide, calcium hydroxide, and water in the blank undergo hydration reaction, and finally generate tobermorite crystals; the steam autoclaving includes heating, constant temperature, and cooling, and the constant pressure is 1.0-1.5MPa; S6, the blank stack trolley with the steam curing pad out of the steam autoclave separates the autoclaved blank and the steam curing pad through a plate suction machine, and the autoclaved blank is continuously dried through a drying machine to make the water content of the blank reach below 9.5%; the dried blank is discharged through a plate belt conveyor, a positioning roller conveyor, and a vacuum plate suction machine, and is stacked into a pile; S7, the dried blank is thickened through a double-sided sander, and is ground and chamfered through an edge grinding and chamfering machine.
5. The process for the production of cementless algeboard panels according to claim 4, characterized in that: In step S4, the pre-curing time is 12-24 hours.
6. The process for the production of cement free algal mud plate as claimed in claim 4 wherein: In step S5, the steam autoclaving includes heating for 2-3 hours, constant temperature for 8-12 hours, and cooling for 2-4 hours.
7. The process for the production of cement-free algea mud plate according to claim 4 or 6, characterized in that: The terminal temperature of the heating in the steam autoclaving is 380-420℃.
Citation Information
Patent Citations
Light-weight calcium silicate plate and preparation method thereof
CN103449773A
Diatom plate and production method thereof
CN108439926A
Kieselguhr plate and preparation method thereof
CN109053108A
Environment-friendly multifunctional diatom plate with moisture resistance, water resistance and flame retardance, and preparation method of diatom plate
CN113045265A
Moisture-controlling construction material
JP2001130946A